Natural cholinesterase inhibitors from Myristica cinnamomea King - Wahab, S.M.A.; Sivasothy, Y.; Liew, Sook Yee; Litaudon, M.; Mohamad, Jamaludin; Awang, Khalijah (Elsevier, 2016)
A new acylphenol, malabaricone E (1) together with the known malabaricones A-C (2–4), maingayones A and B (5 and 6) and maingayic acid B (7) were isolated from the ethyl acetate extract of the fruits of Myristica cinnamomea King. Their structures were determined by 1D and 2D NMR techniques and LCMS-IT-TOF analysis. Compounds 3 (1.84 ± 0.19 and 1.76 ± 0.21 μM, respectively) and 4 (1.94 ± 0.27 and 2.80 ± 0.49 μM, respectively) were identified as dual inhibitors, with almost equal acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes inhibiting potentials. The Lineweaver–Burk plots of compounds 3 and 4 indicated that they were mixed-mode inhibitors. Based on the molecular docking studies, compounds 3 and 4 interacted with the peripheral anionic site (PAS), the catalytic triad and the oxyanion hole of the AChE. As for the BChE, while compound 3 interacted with the PAS, the catalytic triad and the oxyanion hole, compound 4 only interacted with the catalytic triad and the oxyanion hole.